1999
DOI: 10.1179/joc.1999.11.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin, Interleukin-2, Interferon-α and Tamoxifen in Metastatic Melanoma. A Phase II Study

Abstract: Our results, unlike the good results of previous trials, are very poor. Therefore we do not recommend this combination for routine treatment of advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To overcome this intrinsic resistance of the established tumor, combination of immunotherapy and chemotherapy were investigated [52–54]. Even previous studies performed by Naglieri et al [53] and Zagozdzon et al [54] on the immuno-chemotherapy showed contradictory results, the combination in our case was positive. It might depend on the different assemblies of interleukin, cisplatin, and other anticancer factors or diversity of dosage.…”
Section: Results and Disscusionmentioning
confidence: 65%
“…To overcome this intrinsic resistance of the established tumor, combination of immunotherapy and chemotherapy were investigated [52–54]. Even previous studies performed by Naglieri et al [53] and Zagozdzon et al [54] on the immuno-chemotherapy showed contradictory results, the combination in our case was positive. It might depend on the different assemblies of interleukin, cisplatin, and other anticancer factors or diversity of dosage.…”
Section: Results and Disscusionmentioning
confidence: 65%